2007
DOI: 10.1086/519166
|View full text |Cite
|
Sign up to set email alerts
|

Open Reading Frame 8a of the Human Severe Acute Respiratory Syndrome Coronavirus Not Only Promotes Viral Replication but Also Induces Apoptosis

Abstract: Background. A unique genomic difference between human and civet severe acute respiratory syndrome coronaviruses (SARS-CoVs) is that the former has a deletion of 29 nucleotides from open reading frame (orf) 8a that results in the generation of orf8a and orf8b. The objectives of the present study were to analyze antibody reactivity to ORF8a in patients with SARS and to elucidate the function of ORF8a.Methods. Western-blot and immunofluorescent antibody assays were used to detect anti-ORF8a antibody. SARS-CoV HKU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
116
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 45 publications
1
116
1
1
Order By: Relevance
“…Although SARS-CoV 8b gene product could be expressed in vivo when cloned directly behind a promoter [11][12][13]; the expression of 8a and 8b in SARS-CoVinfected cells is still controversial [9,10,13]. As shown above, we were unable to detect the protein expression of sgRNA 8 with the 5 0 viral leader sequence, which corroborated with a recent report on ORF8 expression [13].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Although SARS-CoV 8b gene product could be expressed in vivo when cloned directly behind a promoter [11][12][13]; the expression of 8a and 8b in SARS-CoVinfected cells is still controversial [9,10,13]. As shown above, we were unable to detect the protein expression of sgRNA 8 with the 5 0 viral leader sequence, which corroborated with a recent report on ORF8 expression [13].…”
Section: Resultssupporting
confidence: 91%
“…Ten sgRNAs have been identified [5] and the SARS-CoV accessory proteins 3a, 3b, 6,7a, and 7b can be detected in infected cells or SARS patients besides structural proteins [7,8], while the expression of 8a and 8b is controversial [9][10][11][12][13]. Elucidation of the regulatory mechanism in the translation is important for understanding the pathogenesis of SARS-CoV; however, it is hard to compare the differential translation of sgRNAs because the steady-state level of viral proteins in infected cells reflects the sum of transcription, translation, and the relative stabilities of these transcriptional and translational products.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas Keng et al have demonstrated by indirect immunofluorescence that 8a and 8b are expressed in SARS-CoVinfected Vero E6 cells, Oostra et al were unable to detect 8b in SARS-CoV-infected Vero E6 cells (Oostra et al, 2007;Keng et al, 2006). Although there is no data regarding the expression of 8a or 8b in vivo, Chen et al have identified anti-p8a antibodies in two out of 37 patients with SARS (Chen et al, 2007). Also, different subcellular localizations have been reported for p8a, p8b, and p8ab.…”
Section: Sars-cov P7bmentioning
confidence: 99%
“…Chen et al have shown that SARS-CoV replication is enhanced in cells stably expressing 8a and reduced in cells transfected with siRNA targeting 8a (Chen et al, 2007). However, the results were based on detection of virus RNA and assessment of virus-induced CPE only, and a direct measure of infective virus titre should have been performed.…”
Section: Sars-cov P7bmentioning
confidence: 99%
“…Antibodies to ORF8a have been detected in a small number of SARS patients, proving that the protein is indeed expressed during virus infection [119]. This group also reported that ORF8a not only enhances viral replication, but also induces apoptosis through a mitochondria-dependent pathway [119]. …”
Section: Sars Accessory Proteinsmentioning
confidence: 99%